How career adaptability affects entrepreneurial intention: The chain-mediated roles of entrepreneurial passion and self-efficacy - Jiping Zhang (PLoS ONE, 2025)
This study examined how entrepreneurial passion and entrepreneurial self-efficacy jointly mediate the relationship between career adaptability and entrepreneurial intention. A survey was conducted with 1013 Chinese university students to assess career adaptability, entrepreneurial passion, entrepreneurial self-efficacy, and entrepreneurial intention. The findings indicated that: (1) Career adaptability, entrepreneurial passion, entrepreneurial self-efficacy, and entrepreneurial intention are interconnected in ways that suggest meaningful pathways for enhancing entrepreneurial outcomes; (2) While career adaptability does not directly influence entrepreneurial intention, it has an indirect effect through entrepreneurial self-efficacy and entrepreneurial passion, highlighting the significance of these mediators; (3) Three specific mediation pathways were identified: one through entrepreneurial passion, one through entrepreneurial self-efficacy, and a third involving both factors in a chain-mediated process—where career adaptability enhances entrepreneurial passion, which then fuels entrepreneurial self-efficacy, ultimately boosting entrepreneurial intention. These findings provided deeper insight into how career adaptability shapes entrepreneurial intention and emphasized the importance of nurturing both entrepreneurial passion and entrepreneurial self-efficacy in university entrepreneurship programs. By implementing educational strategies that enhance these factors, educators can better prepare students for entrepreneurial intentions. Although focused on Chinese university students, the findings have global relevance. They offer actionable guidance for government-led entrepreneurship-education systems in higher-education institutions, particularly those in East Asia and Southeast Asia, aimed at fostering adaptive and confident future entrepreneurs.